Screening Strategies for the Discovery of Ion Channel Monoclonal Antibodies. Issue 1 (31st August 2018) - Colley, Caroline S.; England, Elizabeth; Linley, John E.; Wilkinson, Trevor C. I.
Abstract: Ion channels play crucial roles in physiology by modulation of cellular functions that include electrical excitability, secretion, cell migration, and gene transcription. They are an important target class for drug discovery and have historically been targeted using small molecule approaches. A significant opportunity exists to target these channels with antibodies and alternative forms of biologics. Antibodies display high specificity, selectivity, and affinity for their target antigen, thus having the potential to target ion channels very precisely. Nonetheless, isolating antibodies to ion channels is challenging due to the difficulties in expression and purification of ion channels in a format suitable for antibody drug discovery and due to the complexities of screening for function. In this overview, we focus on an array of screening methods, ranging from direct antibody binding screens to complex electrophysiological assays, and describe how these assays can be used to identify functional monoclonal antibodies. We also provide some insights into specific considerations which are required to enable these screens to be used for antibody drug discovery. © 2018 by John Wiley & Sons, Inc.